Acquired von Willebrand syndrome secondary to monoclonal gammopathy: a single-center case series - Quentin Van Thillo; Finn Segers; Jan Brijs; Ulrike Douven; Radha Ramanan; Michel Delforge; Ann Janssens; Cédric Hermans; Johan De Bent; Marc Jacquemin; Thomas Vanassche; Peter Verhamme (Therapeutic Advances in Hematology, 2025)
Acquired von Willebrand syndrome (AVWS) is a well-known complication of a monoclonal gammopathy with a potentially severe bleeding tendency. Treatment with von Willebrand factor (VWF)/factor VIII (FVIII) concentrate yields mixed results in controlling the bleeding diathesis, while the use of intravenous immunoglobulins may be effective. However, clear guidelines for the optimal management of AVWS are lacking. Therefore, we retrospectively analyzed the cases of AVWS secondary to monoclonal gammopathy at the University Hospitals of Leuven. We confirm the beneficial effect of intravenous immunoglobulins in IgG-associated AVWS. For IgM-associated AVWS, we observed better results with the administration of VWF/FVIII concentrate or a combination of therapies. Of note, one patient with IgG-associated AVWS did not respond to immunoglobulins and had mutations in the VWF and fibrinogen gamma chain ( FGG ) genes. This report adds additional cases to the literature of this rare cause of acquired bleeding.